PENGARUH KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP PERILAKU KERJA INOVATIF PADA INDUSTRI 4.0 - Masduki Asbari; Priyono Budi Santoso; Agus Purwanto (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2019)
In the competitive business world today, many industries face the flux of rapid change, especially in the industrial revolution 4.0. Therefore companies should focus on innovative work behavior (IWB) in order to gain a competitive advantage. This research tested the effect of transformational leadership and organizational climate on the innovative work behavior by taking a manufacturing industry in Tangerang as a case. Population and sample is 160 employees with census method. Data collection technique is using questionnaire with likert scale. The instrument used to measure transformational leadership is an adaptation of Podsakof et al (1990). The instrument for measuring organizational climate adopted from the Organizational Climate Measure (OCM) developed by Patterson et al (2005). Meanwhile, to measure innovative work behavior adapted from (Jong & Hartog, 2008). Analysis from this study is using SEM (Structural Equation Model) with SmartPLS version 3.0 as a statistic tools. The result was transformational leadership gave a positive effect and significant on the organizational climate. The transformational leadership and the organizational climate also gave a positive effect and significant on the innovative work behavior partially and simultaneous.